Usage of running drills in an interval training program: Implications related to biomechanical parameters of running - Azevedo, A. P. S.; Mezêncio, B.; Valvassori, R.; Anjos, F. O. M.; Barbanti, V. J.; Amadio, A. C.; Serrão, J. C. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to investigate the effects of running drills during an interval training program on biomechanical parameters of running. Thirty recreational runners, divided into 2 groups (control group and experimental group [EG]), were submitted to a 15-week interval training, but only EG performed running drills in the training. The test sessions were accomplished before and after intervention. Spatiotemporal and kinetic variables were analyzed at 2 speeds: maximum (Smax) and comfortable (Scomf). For moment effect, significant increases were observed for Scomf (8.9%) and Smax (10.7%) after training. Variables related to mechanical load were also higher after training for both speeds (LR1: 16.4% and Imp75: 7.8% at Scomf; LR1: 21.4% and Imp75: 8.1% at Smax). For training approach effect, higher value of Imp75 was observed in EG (10.1% at Scomf and 11.9% at Smax, without performance improvements). Also, EG presented higher values of Fy2 (6.7% at Scomf and 6.1% at Smax) and FT (13.3% at Scomf), variables related to the center of mass oscillation. As a conclusion, including running drills in a 15-week interval running training seems not to be an efficient procedure to improve parameters related to mechanical load and performance.